Identification of physically demanding tasks performed during bushfire suppression by Australian rural firefighters - Phillips, M.; Payne, W.; Lord, C.; Netto, Kevin; Nichols, D.; Aisbett, B. (Elsevier, 2012)
Purpose: To identify and characterize the physically demanding tasks undertaken during multi-day wildfire (known as bushfire in Australia) suppression by Australian rural firefighters. Methods: During semi-structured group interviews, thirty-one experienced male firefighters reviewed 53 firefighting tasks that could be performed during tanker-based bushfire suppression. Participants were asked to nominate the most physically demanding tasks and then define their typical frequencies, durations, operational importance and the dominant actions and activity types in each task. Results: Seven tasks were identified as physically demanding. They were further categorized into three hose and four handtool (e.g., rakehoe) related activities. These tasks were assessed as moderately important to critical and were thought to occur less than one up to 700 times in a four-month bushfire ‘season’. Each task’s duration was estimated to last approximately 2–30 min depending on the task. Dominant actions were carry, drag, dig/rake actions in seven, three and four of the demanding tasks, respectively. ‘Strength-endurance’ was the dominant activity type for five of the seven tasks. Conclusion: Seven fireground tasks, three using a hose and four using handtools were classified as physically demanding by incumbent firefighters. The combination of hose and handtool work indicates that the tanker-based bushfire suppression tactics used by Australian rural firefighters appears to be a hybrid of structural and wildfire firefighting techniques and may require a dedicated physiological analyses before the job demands for these firefighters can be quantified.